Eligibility for treatment and angiographic features at the early stage of exudative age related macular degeneration. Issue 6 (1st June 2002) - Haddad, W M; Coscas, G; Soubrane, G
Abstract : Aims: To determine the eligibility for laser photocoagulation treatment or for photodynamic therapy (PDT) with verteporfin in eyes at the earliest stage (first month of symptoms) of exudative age related macular degeneration (AMD) based on fluorescein angiographic (FA) features; to evaluate the potential contribution of indocyanine green angiography (ICG-A) for occult choroidal neovascularisation (CNV) at this stage. Methods: Retrospective review of 252 consecutive patients (269 eyes) examined within the first month of symptoms of exudative AMD. Results: On FA, 97 eyes (36%) had classic CNV alone. Occult CNV associated with fibrovascular retinal pigment epithelium detachments (PEDs) was observed in 71 eyes (26%) and without fibrovascular PED in 101 eyes (38%). 91 eyes (34%) met the Macular Photocoagulation Study criteria for laser photocoagulation. 53 eyes (20%) met the Verteporfin In PDT (VIP) or Treatment of AMD with PDT (TAP) studies criteria. By ICG-A, occult CNV was visualised as focal spots in 49% of eyes examined within 15 days v 32% of eyes examined between 16 and 30 days after the onset of symptoms (p=0.07). 8.5% of late staining plaques disclosed in eyes examined within 15 days were combined with focal spots v 36% in eyes examined between 16 and 30 days (p<0.01). Conclusions: Early examination of eyes with exudative AMD would allow the treatment of 47% of eyes. 60% of eyes with subfoveal CNV would be eligible for PDT with verteporfin. Up to half of eyes with occult CNV would be converted by ICG-A into well delineated focal spots.